2014
DOI: 10.1371/journal.pone.0088027
|View full text |Cite
|
Sign up to set email alerts
|

How Current Clinical Practice Guidelines for Low Back Pain Reflect Traditional Medicine in East Asian Countries: A Systematic Review of Clinical Practice Guidelines and Systematic Reviews

Abstract: ObjectivesThe aims of this study were to investigate whether there is a gap between evidence of traditional medicine (TM) interventions in East-Asian countries from the current Clinical Practice Guidelines (CPGs) and evidence from current systematic reviews and meta-analyses (SR-MAs) and to analyze the impact of this gap on present CPGs.MethodsWe examined 5 representative TM interventions in the health care systems of East-Asian countries. We searched seven relevant databases for CPGs to identify whether core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…70 In 2013 and 2015, there were two systematic reviews 71 drew a conclusion that cupping therapy is promising 72 for pain [10,12]. In 2014, a systematic review of tra-73 ditional medicine in east asian countries weakly rec-74 ommended cupping therapy for both sub-acute and 75 chronic LBP [11]. In 2015, a review about all aspects 76 of TCM for neck pain (NP) and LBP indicated that 77 cupping could be efficacious in pain and disability for 78 chronic NP or chronic LBP in the immediate term [13].…”
Section: Cupping Therapy Is a Common Therapy In Traditionalmentioning
confidence: 99%
“…70 In 2013 and 2015, there were two systematic reviews 71 drew a conclusion that cupping therapy is promising 72 for pain [10,12]. In 2014, a systematic review of tra-73 ditional medicine in east asian countries weakly rec-74 ommended cupping therapy for both sub-acute and 75 chronic LBP [11]. In 2015, a review about all aspects 76 of TCM for neck pain (NP) and LBP indicated that 77 cupping could be efficacious in pain and disability for 78 chronic NP or chronic LBP in the immediate term [13].…”
Section: Cupping Therapy Is a Common Therapy In Traditionalmentioning
confidence: 99%
“…14 ECA. 2110 pacientes Evalúa la evidencia de la eficacia de la acupuntura para LBP inespecífico en comparación con las terapias simuladas o placebo Disminución significativa en dolor comparando acupuntura simulada y placebo No existen diferencias en cuanto a funcionalidad Moderada evidencia científica de la eficacia de acupuntura en términos de reducción de dolor inmediatamente tras el tratamiento para LPB inespecífico subagudo y crónico (cuando se compara con acupuntura simulada o placebo) Nishishinya, 2019 (10) Revisión de la eficacia del tratamiento con acupuntura comparada con otras intervenciones, en el manejo del dolor y la función física en las enfermedades reumáticas con afectación axial que cursan con dolor cervical y lumbar: 5 RS LBP agudo: acupuntura tiene un efecto potencial positivo, pero no tanto en la funcionalidad cuando se compara con acupuntura simulada. LBP crónico: acupuntura mejora el dolor, tanto de forma inmediata como a corto plazo, aunque no tanto la funcionalidad, cuando se compara con otras terapias simuladas Acupuntura asociada a terapias convencionales a corto plazo, frente a terapias convencionales solas La acupuntura es eficaz en LBP agudo y crónico como primera línea terapéutica, comparada con placebo, y como coadyuvante de otros tratamientos convencionales Los resultados no son concluyentes en radiculopatía, estenosis de canal lumbar y espondilitis anquilosante general previo a la aparición del LBP, resultado fisiológico tras la intervención, medidas globales de mejoría y vuelta al trabajo.…”
Section: Discussionunclassified
“…One article published in 2014 identified 13 guidelines and 22 systematic reviews issued by East Asian countries on traditional medicine (including acupuncture, moxibustion, cupping, herbal medicine, TCM, manual therapy and Tuina ) for low back pain. 87 This study suggested that the current CPGs do not fully reflect the evidence for traditional medicine interventions and concluded that, as relevant studies, systematic reviews and meta-analyses are conducted and the evidence increases, the current evidence on acupuncture, herbal medicine and manual therapy should be reconsidered in the process of developing or updating relevant CPGs. Similarly, in the UK, a recent study of NHS Western medical clinical guidelines issued by the National Institute for Health and Care Excellence demonstrated a low proportion of CPGs mentioning at least one CAM.…”
Section: Discussionmentioning
confidence: 99%